The Role of Industry-Based Tourism in Business Development in Indonesia - Andin Rusmini (Lembaga Penelitian Publikasi dan Pengabdian Masyarakat LSPR, 2022)
Tourism has a lot of origins about tourist attractions, as well as the people. The community is basically an important role in the realization of a tourism place. There are local people who act as owners and managers and run their business in the tourism area, as well as the community as visitors from tourism places. In tourism there is a tourism industry in it, which is one of the largest and fastest growing industries in the world. The tourism industry is one of the largest and fastest growing industries in the world. The Tourism Industry is very different from other industries, such as the clothing industry and the agricultural industry, the Hospitality Industry is more likely to operate in providing services. Tourism is part of business development in Indonesia, ranging from hotels in it, modern tourism, marine tourism and other tours, which play a role in the progress and development of business in Indonesia. The increasing population growth, coupled with increasing economic needs, has made people develop creativity from their communities to develop businesses based on the tourism industry.